2020
DOI: 10.1177/1177180120919166
|View full text |Cite
|
Sign up to set email alerts
|

Seeing the unseen: evidence of kaupapa Māori health interventions

Abstract: Māori in Aotearoa have higher incidence, prevalence and mortality from chronic disease. The dominant narrative in Aotearoa about the reasons for Māori ill health neglects to acknowledge the history of colonisation and failures of the health system, alongside the holistic view of health taken by Māori focusing on collective, whānau-based outcomes. In this article, we review health interventions for chronic disease that have a kaupapa Māori philosophical basis. Our findings demonstrate that there is no clear pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 32 publications
(28 reference statements)
0
41
0
Order By: Relevance
“…Also, it is possible that there is relevant unpublished information that is not included in this review. Māori have a long history of self-determination and finding solutions for their own communities (Pipi et al, 2003) and a complicated history with Western research (Rolleston et al, 2020). It is therefore possible that there is knowledge held within Māori communities that has not been captured in the published literature.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, it is possible that there is relevant unpublished information that is not included in this review. Māori have a long history of self-determination and finding solutions for their own communities (Pipi et al, 2003) and a complicated history with Western research (Rolleston et al, 2020). It is therefore possible that there is knowledge held within Māori communities that has not been captured in the published literature.…”
Section: Limitationsmentioning
confidence: 99%
“…There is also evidence to suggest that autistic individuals from minority groups are less likely to access evidence-based treatments (Baumann et al, 2015;Smith et al, 2020). This may be especially true for indigenous populations who have a well documented history of health disparities across a broad range of outcomes, including access to healthcare (Rolleston et al, 2020). Furthermore, some families may look to support systems within their wider families or communities, rather than seeking an interventionist treatment approach.…”
Section: Rationalementioning
confidence: 99%
“…28 The broader literature has demonstrated that equitable health care delivery for Māori (and Pacific), such as with the immunisation programme, will require Māori governance and leadership, culturally-responsive health care delivery, resourcing of trusted community providers, and supports for access. [29][30][31][32] It is known that the current primary health care system in New Zealand fails to deliver on these points, and fails to meet legal obligations to Māori. 33 Ongoing attention needs to be paid to the critical combination of heightened risk of mortality and morbidity from COVID-19 disease for Māori (and Pacific) populations 13 and the systemic racism within New Zealand's health system that will result in inability to translate rates of vaccination intention into vaccine access and uptake.…”
Section: Discussionmentioning
confidence: 99%
“…In this light, Kaupapa Māori research (KMR) methodology advocates for ethical cogovernance and leadership 'by Māori, for Māori,' as western-centric initiatives have not been suitable to address the inequities in Māori health. 27 KMR has grown exponentially and the work of Māori scholars has seen it evolve into a space of renaissance within academia. 28 Traditional western research paradigms are privileged and upheld as 'all knowing,' leading to criticisms of KMR being of limited focus and unsuitable in quality improvement, despite it providing greater health quality and health outcomes for Māori.…”
Section: Western and Indigenous Epistemologiesmentioning
confidence: 99%